A center of excellence model for LGBT patient care. Issue 6 (November 2016) - Lockhart, Lisa; Davis, Charlotte
Abstract : Together we can be a positive link to change perceptions about healthcare delivery for our lesbian, gay, bisexual, and transgender patients and families.